Preliminary study cocos nucifera frond powder treated with sulphuric acid as lead adsorbent / Nur Fadhilah Hassan - Hassan, Nur Fadhilah (Faculty of Applied Sciences, 2017)
This preliminary study about the availability of coconut frond treated with Sulphuric acid used to check its characteristics in removing lead in lead aqueous solution by characteristics of pH slurry, pH zero point charge and FTIR analysis. The treatment of sulphuric acid on coconut frond by electrophilic addition reaction The maximum adsorption of the aqueous lead solution was at dosage of 0.08 g with percent removal of 99.78 %. An initial pH in the range of 6-9 was favorable for the lead removal by the natural adsorbents. Adsorption can be used in removing heavy metal using treated coconut frond with sulphuric acid.